Tantalizing Flavors of Sri Lanka: Unraveling Tourist Perceptions of Sri Lankan Food Culture - Anuja Lokeshwara; Gayan Chathuranga Bandara; Chalani Lakshitha Kuruppu (Centre For Tourism Planning and Development, 2023)
This research paper explores the perception of tourists regarding Sri Lankan food and its potential for culinary tourism. Sri Lanka, known for its unique flavors and culinary traditions, has a rich gastronomy that remains largely untapped in terms of culinary tourism. The study aims to gain insights into tourists' experiences, preferences, and overall perceptions of Sri Lankan cuisine. The literature review examines the importance of food flavor in shaping tourist satisfaction and its role in gastro tourism worldwide. It also explores the fusion of tradition and gastro tourism in different countries and perceptions towards traditional food experiences. Tourists' expectations and the overall culinary experience are also discussed, highlighting the significance of food in shaping their perception of a destination. The study adopted a qualitative approach and word cloud and thematic analysis were conducted in data analysis. The findings reveal tourists' perceptions of Sri Lankan food, emphasizing its flavors, authenticity, and ability to surpass expectations. Based on these perceptions, recommendations are provided to promote and enhance the gastronomic offerings of Sri Lanka, including culinary promotions, preservation of authenticity, and collaborative partnerships. The conclusion summarizes the themes that emerged from the study and emphasizes the importance of understanding tourists' perceptions to promote culinary tourism and enhance visitor experiences in Sri Lanka. Overall, this research contributes valuable insights to the development of culinary tourism in Sri Lanka and showcases the potential of Sri Lankan cuisine as a captivating and immersive culinary experience for tourists.